Population oscillations and energy reserves in planktonic cladocera and their consequences to competition - Goulden, Clyde E. (1980)
Time lags in an individual's response to decreased food densities are responsible for oscillations in laboratory populations of Daphnia galeata mendotae. Visible energy reserves of triacylglycerols accumulate in the body of animals at low population densities when food is abundant and are later metabolized at high population densities when food is scarce to temporarily sustain activity and reproduction. After these energy reserves are metabolized many individuals, primarily juveniles, starve and die. The length of the time lags is a function of the amount of energy reserve accumulated in the individual. Because this sustained activity and reproduction further decreases food concentrations to very low levels, individuals of a second smaller-body-sized species, Bosmina longirostris, that do not have sufficient energy reserves quickly starve and die. Thus the accumulation of energy reserves in individuals underlies the time lags important in causing population oscillations and has consequences to interspecific competition.